SIMULASI SISTEM PENGATURAN LALU LINTAS OTOMATIS DENGAN KARAKTERISTIK KERAPATAN PADA SIMPANG TIGA DAN SIMPANG EMPAT MENGGUNAKAN ALGORITMA MILOZA - Wamiliana Wamiliana; Izzatuz Zakiyah Mukhtarisa; Ossy Dwi Endah Wulandari (Universitas Lampung, 2013)
Nowadays, the traffic control system already done computerized. However, usually the system is set without considering density of the changing vehicles. In this research, an algorithm developed to solve the problem of traffic control is still constant and manual (fixed time traffic). The algorithm is called Miloza algorithm. Miloza algorithm is an algorithm used to find the optimum solution of traffic control based on density characteristics of the vehicle. The purpose of this research is to make a simulation of automatic control system for traffic light with density characteristics at the three and four junctions using MilozaAlgorithm as an alternative solution. The simulation application is made using visual basic programming language and the method of application development used is prototype method.Keywords: traffic control, algorithm, simulation